Quality indicators for the diagnosis and management of pediatric tonsillitis. (December 2020) - Cottrell, Justin; Yip, Jonathan; Campisi, Paolo; Chadha, Neil K.; Damji, Ali; Hong, Paul; Lachance, Sophie; Leitao, Darren; Nguyen, Lily HP.; Saunders, Natasha; Strychowsky, Julie; Yunker, Warren; et al.
Abstract: Introduction: Pediatric tonsillitis is encountered frequently across specialties, and while high quality guidelines exist, there is persistent evidence of care which is not evidence based, including antibiotic overprescribing and surgical practice variability. Quality indicators (QIs) can be utilized for initiatives to improve the quality of care and subsequent patient outcomes. We sought to develop pediatric tonsillitis QIs that are applicable across specialties and that cover aspects of both diagnosis and the spectrum of management options. Methods: A guideline-based approach to QI development was employed. Candidate indicators (CIs) were extracted from international guidelines deemed high quality by two reviewers and evaluated by an eleven-member expert panel consisting of otolaryngology – head & neck surgeons, a pediatrician and a family physician. The final QIs were selected utilizing a modified RAND/UCLA appropriateness methodology. Results: Twenty-six CIs were identified after initial literature review. After the first round of evaluations, the panel agreed on thirteen candidate indicators as appropriate QIs. A subsequent expert panel meeting provided a platform to discuss areas of disagreement, discuss any recently published research, and to brainstorm additional CIs not identified from the guideline extraction. Following the second round of evaluations, the expert panel agreed upon sixteen QIs as appropriate measures of high-quality care. Conclusions: This study proposes sixteen QIs developed through a multidisciplinary lens to guide practitioners in the diagnosis and management of pediatric tonsillitis. These QIs can be used to improve transparency, accountability, and provide objective data to assist future quality improvement initiatives.